2010
DOI: 10.1002/bjs.7096
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of multidetector computed tomography in identifying poor prognostic factors in colonic cancer

Abstract: As the ability of CT to identify node status is poor, the depth of tumour invasion beyond the muscularis propria is the most accurate way to identify patients with a poor prognosis who may be suitable for neoadjuvant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 54 publications
4
59
1
Order By: Relevance
“…16 The accuracy of MRI in this study for the identification of EMVI was again good at 74% for Reader 1 and 69% for Reader 2. The accuracy of CT for the identification of EMVI is reported in three previous studies; Burton et al reported an accuracy of 55% for Observer 1 and 61% for Reader 2, 31 Dighe et al 32 reported an accuracy of 70% and Rollven et al reported an accuracy of 78% for Reader 1 and 69% for Reader 2. Rollven et al also reported the accuracy of MRI of 78% and 82%.…”
Section: Discussionmentioning
confidence: 90%
“…16 The accuracy of MRI in this study for the identification of EMVI was again good at 74% for Reader 1 and 69% for Reader 2. The accuracy of CT for the identification of EMVI is reported in three previous studies; Burton et al reported an accuracy of 55% for Observer 1 and 61% for Reader 2, 31 Dighe et al 32 reported an accuracy of 70% and Rollven et al reported an accuracy of 78% for Reader 1 and 69% for Reader 2. Rollven et al also reported the accuracy of MRI of 78% and 82%.…”
Section: Discussionmentioning
confidence: 90%
“…20,21 However, only one report described CT-pathological correlation of venous invasion in small-or medium-sized veins. 22 In that report, the interobserver agreement for CT detection of venous invasion was poor, and the architecture of the vessel wall did not seem to be confirmed pathologically by additional special staining such as Elastica van Gieson stain (EVG). We thought that the agreement between radiologists was limited by poor understanding of the histology of MVI in colorectal cancer.…”
mentioning
confidence: 88%
“…In a prospective audit of 84 patients with colon cancer undergoing pre-operative multidetector computerised tomography (CT) scanning, the accuracy, sensitivity and specificity for detection of LN disease was 58% [95% confidence interval (CI) 48% to 68%], 64% (95% CI 48% to 77%) and 53% (95% CI 39% to 67%), respectively, with poor interobserver agreement for node status. 15 Further, when nodes were assessed according to tumour node metastasis classification by separating into N0, N1 and N2 disease, the accuracy, sensitivity and specificity fell to 50% for all values. A meta-analysis of 19 studies has reported an overall sensitivity and specificity for CT-detected malignant LNs to be 70% (95% CI 59% to 80%) and 78% (95% CI 66% to 86%), respectively, with a diagnostic odds ratio of 8.1 (95% CI 4.7 to 14.1).…”
Section: Preoperative Lymph Node Stagingmentioning
confidence: 89%